Transformasi TQM dalam Pendidikan Digital: Menuju Sekolah Adaptif dan Organisasi Pembelajar 5.0: Total Quality Management Transformation in Digital Education: Towards Adaptive Schools and Learning Organizations 5.0 - Sudiansyah, Sudiansyah (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
In addressing the challenges of Industry 5.0, the education system is compelled to undergo a fundamental transformation through a comprehensive, adaptive, and humanistic quality management approach. This research aims to explore strategies for quality management transformation and educational standardization in the digital era based on the principles of Total Quality Management (TQM), with a focus on leadership, adaptive curriculum, and quality assurance systems to foster learning organizations. Employing a multidisciplinary qualitative approach and a multiple case study method, data were collected through in-depth interviews, observation, and documentation, and subsequently validated via member checking. The findings indicate that the eight TQM principles are implemented contextually with varying degrees of effectiveness. Schools that apply transformative leadership, technology integration, and active collaboration with the business and industry sector are demonstrably better prepared to become Industry 5.0-based learning organizations. In conclusion, the success of educational transformation hinges on the synergy among leadership, organizational culture, and a quality system that is responsive to change. This study offers theoretical and practical contributions to the formulation of sustainable and contextually relevant strategies for enhancing educational quality.